The new modification of a solar still chamber with hollow glass: An experimental comparison between perpendicular and inline hollow glass configurations: Referred to by: https://doi.org/10.31603/mesi.17044 - Eko Prasetya Budiana; Muhamad Dwi Septiyanto; Satria Auliansyah; Naufal Rizky Sayyid; Indri Yaningsih; Syamsul Hadi (Mechanical Engineering for Society and Industry, 2025)
Researchers around the world are conducting comprehensive studies on conventional single-slope solar stills (CS4). Recent trends have focused on minimizing heat loss and improving the productivity of these systems, particularly through modifications to the CS4 chamber. This present study examines the modified chambers of solar stills utilizing Perpendicular Hollow Glass Solar Still (PHGSS) and Inline Hollow Glass Solar Still (IHGSS). It provides a comprehensive analysis of the enhancements, highlighting key aspects such as productivity, energy balance, and efficiency, as well as introducing a potential new condensation site. To ensure accuracy and reliability, the results are validated using the coefficient he/hc from a previous study, which reported a margin of error of 7.76%. The application of hollow glass has proven its ability to produce distillate condensation due to the temperature gradient present between the inner surface of the hollow glass and the cavity it encloses. Moreover, the production and efficiency of both inline and perpendicular hollow glass highly exceeds those of conventional CS4.